Pets, People, and Pragmatism. - McKenna, Erin (American philosophy., 2013)
Pragmatism is used to explore human beings' relationships with horses, dogs, and cats. This results in some surprising conclusions such as respectful relations may require humans to continue in some interactions that include training and work. While most animal rights advocates call for the abolition of all such use, a pragmatist needs to respect the history of these beings and find ways for them to express themselves.